2021
DOI: 10.3390/ijerph18031059
|View full text |Cite
|
Sign up to set email alerts
|

Family Orchards and Health-Related Quality of Life in the Elderly. A Protocol for a Study in Las Hurdes (Spain) Based on an Ethnographic Approach

Abstract: Demographic evolution is resulting on an aged population increment in Spain. This growth has been more relevant in rural areas, where the population has traditionally lived under hard socio-economic conditions and leveraging the natural resources such as food from family orchards to survive. Studies that have investigated the possibilities and uses of these traditional family orchards today in relation to health-related quality of life in the elderly are scarce. Based on a previous ethnography, this mixed rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The afforestation policy of the Franco regime (1940–1975) resulted in massive pine plantations which are positively correlated with forest fire occurrence (Iriarte-Goñi and Ayuda 2018 ). Since the 1950s, industrialisation and socio-economic crises have fueled outmigration, leaving a population of rising average age (Madruga et al 2021 ). This rural depopulation also caused land abandonment, abandonment of livestock grazing and resulting in forest encroachment, and in consequence flammable biomass accumulation and a more fires (Iriarte-Goñi and Ayuda 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The afforestation policy of the Franco regime (1940–1975) resulted in massive pine plantations which are positively correlated with forest fire occurrence (Iriarte-Goñi and Ayuda 2018 ). Since the 1950s, industrialisation and socio-economic crises have fueled outmigration, leaving a population of rising average age (Madruga et al 2021 ). This rural depopulation also caused land abandonment, abandonment of livestock grazing and resulting in forest encroachment, and in consequence flammable biomass accumulation and a more fires (Iriarte-Goñi and Ayuda 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The most significant component of family resources is family income, and some studies have shown that elderly people with low family income have poorer health ( Hinata et al, 2021 ). Family orchards are one family resource that affects family economic income, and orchard work contributes to improved physical health as well as mental health ( Madruga et al, 2021 ). At present, adult children are primarily responsible for home care of the elderly in China, but urban development has resulted in many adult children migrating away from their families.…”
Section: Introductionmentioning
confidence: 99%